Adhesive composition and adhesive sheet for flexible displays
The adhesive composition for flexible displays, using a (meth)acrylic copolymer and metal chelate/alkoxide crosslinking agents, addresses the issue of inadequate recovery from bending, ensuring adhesion and preventing defects in flexible displays.
Patent Information
- Application Number
- JP2020197160
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-27
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2040-11-27
AI Technical Summary
Conventional adhesive layers in flexible displays fail to recover adequately from bending, leading to potential lifting or peeling at the interface and appearance defects such as cracks and waviness.
An adhesive composition for flexible displays containing a (meth)acrylic copolymer and a crosslinking agent, where the crosslinking agent is a metal chelate or metal alkoxide compound, with specific ratios of crosslinkable functional groups and points, enhancing the adhesive's restorability and strength.
The adhesive composition ensures that flexible displays maintain adhesion and prevent defects like lifting or peeling at bent portions, even with repeated bending, by promoting recovery and maintaining adhesive strength.
Smart Images

Figure 0007602354000009 
Figure 0007602354000010 
Figure 0007602354000011
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition used in a flexible display, and more particularly to an adhesive composition forming an adhesive used to bond one flexible member to another flexible member. [Background technology]
[0002] Adhesives are generally used to bond components constituting various displays and touch panels of televisions, mobile phones, smartphones, etc. The adhesives are provided, for example, in the form of a substrate-attached adhesive sheet having an adhesive layer on a supporting substrate, or a substrate-less adhesive sheet having no supporting substrate, and are used to bond the components together.
[0003] Meanwhile, in recent years, flexible displays that are repeatedly bent and used have been attracting attention in image display devices such as liquid crystal display devices and organic electroluminescence (OLED) display devices. Flexible displays include foldable displays that can be folded and rollable displays that can be rolled up into a cylindrical shape, and are expected to be used in mobile devices such as smartphones and tablet devices, and storable stationary displays.
[0004] In such flexible displays, for example, Patent Document 1 discloses an adhesive material for bonding a flexible member that constitutes a component that is repeatedly bent and stretched to another flexible member, which is for use in repeatedly bending devices, in which the ratio of the shear stress 60 seconds after 1000% displacement to the maximum shear stress when one side and the other side of the adhesive layer are displaced 1000% in opposite directions, and the gel fraction are controlled within a predetermined range (see Patent Document 1 (Claim 1)). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2019-108498 A Summary of the Invention [Problem to be solved by the invention]
[0006] In a conventional flexible display having an adhesive layer, when the display is repeatedly bent, the adhesive layer does not fully recover from the bent state to the original state, and therefore, when the display is repeatedly bent, there is a risk of the interface between the adhesive layer and the bendable member at the bent portion becoming lifted or peeled off, or the bent portion appearing wavy, resulting in poor appearance.
[0007] The present invention has been made in consideration of the above circumstances, and has an object to provide an adhesive composition capable of forming an adhesive material (adhesive layer) having excellent restorability and adhesive strength. [Means for solving the problem]
[0008] The adhesive composition for flexible displays of the present invention, which has been able to solve the above problems, comprises a (meth)acrylic copolymer and a crosslinking agent, the crosslinking agent comprises at least one organometallic compound selected from the group consisting of metal chelate compounds, metal acylate compounds, and metal alkoxide compounds, the (meth)acrylic copolymer has a crosslinkable functional group that reacts with the organometallic compound, the amount of the crosslinkable functional group per unit mass of the (meth)acrylic copolymer is 5 μmol / g to 1500 μmol / g, the total amount of crosslinkable points of the crosslinking agent per unit mass of the (meth)acrylic copolymer is 7 μmol / g to 60 μmol / g, and the amount of crosslinkable points of the organometallic compound is 65 mol% or more relative to 100 mol% of the total amount of crosslinkable points of the crosslinking agent.
[0009] The adhesive composition for flexible displays of the present invention has a small amount of crosslinkable functional groups in the (meth)acrylic copolymer, contains a specific organometallic compound as a crosslinking agent, and has a high ratio of crosslinkable points of the organometallic compound among the crosslinkable points of the crosslinking agent. By configuring in this way, the adhesive material formed from the adhesive composition has a high recovery rate after deformation and excellent adhesive strength. Therefore, by using the adhesive composition for flexible displays of the present invention, the occurrence of poor appearance such as cracks and waviness can be suppressed without the occurrence of lifting or peeling at the interface between the adhesive layer and the flexible member at the bending portion of the flexible display. Effect of the Invention
[0010] By using the adhesive composition for flexible displays of the present invention, an adhesive material (adhesive layer) having excellent resilience and adhesive strength can be formed. Therefore, even if the flexible display is repeatedly bent, the interface between the adhesive layer and the flexible member at the bent portion does not lift or peel, and a flexible display can be manufactured in which the occurrence of defective appearance such as cracks and waviness can be suppressed. [Brief description of the drawings]
[0011] [Figure 1] 1 is a schematic cross-sectional view of an example of a pressure-sensitive adhesive sheet of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of an example of a flexible laminated member of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view of an example of a flexible laminated member of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, a preferred embodiment of the present invention will be described. However, the following embodiment is merely an example, and the present invention is not limited to the following embodiment.
[0013] In the present invention, "(meth)acrylic" refers to "at least one of acrylic and methacrylic". "(meth)acrylate" refers to "at least one of acrylate and methacrylate". "(meth)acryloyl" refers to "at least one of acryloyl and methacryloyl". "Vinyl monomer" refers to a monomer having a radically polymerizable carbon-carbon double bond in the molecule. "Structural unit derived from vinyl monomer" refers to a structural unit in which the radically polymerizable carbon-carbon double bond of a vinyl monomer is polymerized to a carbon-carbon single bond. "Structural unit derived from (meth)acrylate" refers to a structural unit in which the radically polymerizable carbon-carbon double bond of a (meth)acrylate is polymerized to a carbon-carbon single bond. "Structural unit derived from (meth)acrylic monomer" refers to a structural unit in which the radically polymerizable carbon-carbon double bond of a (meth)acrylic monomer is polymerized to a carbon-carbon single bond.
[0014] [Adhesive composition for flexible displays] The pressure-sensitive adhesive composition for flexible displays of the present invention contains a (meth)acrylic copolymer and a crosslinking agent.
[0015] ((Meth)acrylic copolymer) The pressure-sensitive adhesive composition contains a (meth)acrylic copolymer (A) (hereinafter, may be simply referred to as "copolymer (A)"). The (meth)acrylic copolymer may be any copolymer that contains structural units derived from (meth)acrylic monomers as the main component (50% by mass or more), and may contain structural units derived from vinyl monomers other than (meth)acrylic monomers. The content of structural units derived from (meth)acrylic monomers in the copolymer (A) is preferably 80% by mass or more, more preferably 90% by mass or more, based on 100% by mass of the entire copolymer. The copolymer (A) may be composed only of structural units derived from (meth)acrylic monomers.
[0016] The (A) copolymer is preferably a (meth)acrylate copolymer. The (meth)acrylate copolymer may be any copolymer that contains a structural unit derived from a (meth)acrylate as the main component (50% by mass or more), and may contain a structural unit derived from a vinyl monomer other than a (meth)acrylate. The (meth)acrylate is an ester compound formed from (meth)acrylic acid and a compound having a hydroxyl group. The content of the structural unit derived from a (meth)acrylate in the (A) copolymer is preferably 80% by mass or more, more preferably 90% by mass or more, based on 100% by mass of the entire copolymer.
[0017] The (A) copolymer has a crosslinkable functional group that reacts with an organometallic compound contained in the (B) crosslinking agent described later. The crosslinkable functional group reacts with an organometallic compound contained in the (B) crosslinking agent described later, but may also react with other crosslinkable points of the (B) crosslinking agent. The crosslinkable functional group may be one type or two or more types. Examples of the crosslinkable functional group include one or more types selected from the group consisting of a hydroxy group, a carboxy group, and an epoxy group, and are preferably a hydroxy group and / or a carboxy group. Among these, it is more preferable to contain a carboxy group from the viewpoint of obtaining good restorability by reacting with the crosslinkable points of the organometallic compound.
[0018] The total amount of crosslinkable functional groups per unit mass of the copolymer (A) is preferably 5 μmol / g or more, more preferably 50 μmol / g or more, even more preferably 100 μmol / g or more, particularly preferably 150 μmol / g or more, and is preferably 1500 μmol / g or less, more preferably 1000 μmol / g or less, even more preferably 700 μmol / g or less, and particularly preferably 500 μmol / g or less. If the total amount of crosslinkable functional groups is 5 μmol / g or more, the durability of the resulting adhesive layer is excellent, and if it is 1500 μmol / g or less, the adhesive layer has excellent adhesion to the adherend.
[0019] When the copolymer (A) has a carboxy group, the amount of the carboxy group per unit mass of the copolymer (A) is preferably 5 μmol / g or more, more preferably 50 μmol / g or more, even more preferably 100 μmol / g or more, and particularly preferably 150 μmol / g or more, and is preferably 1500 μmol / g or less, more preferably 1000 μmol / g or less, even more preferably 700 μmol / g or less, and particularly preferably 500 μmol / g or less.
[0020] When the copolymer (A) has hydroxy groups, the amount of hydroxy groups per unit mass of the copolymer (A) is preferably 5 μmol / g or more, more preferably 50 μmol / g or more, even more preferably 100 μmol / g or more, and particularly preferably 150 μmol / g or more, and is preferably 1500 μmol / g or less, more preferably 1000 μmol / g or less, even more preferably 700 μmol / g or less, and particularly preferably 500 μmol / g or less.
[0021] The copolymer (A) has a crosslinkable functional group. That is, the copolymer (A) contains a structural unit (a-1) having a crosslinkable functional group in its structure. The structural unit (a-1) having the crosslinkable functional group may be only one type, or may have two or more types. The crosslinkable functional group may be in any of a structural unit derived from a (meth)acrylic monomer (preferably a (meth)acrylate monomer and / or (meth)acrylic acid) and a structural unit derived from a vinyl monomer other than a (meth)acrylic monomer. That is, the structural unit (a-1) having the crosslinkable functional group may be a structural unit derived from a (meth)acrylic monomer (preferably a (meth)acrylate monomer and / or (meth)acrylic acid) having a crosslinkable functional group, or a structural unit derived from a vinyl monomer other than a (meth)acrylic monomer having a crosslinkable functional group.
[0022] The content of the structural unit (structural unit (a-1) having a crosslinkable functional group) derived from a vinyl monomer having a crosslinkable functional group in the copolymer (A) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, particularly preferably 3% by mass or more, and preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, and particularly preferably 8% by mass or less, based on 100% by mass of the entire copolymer. If the content of the structural unit (a-1) is within the above range, an adhesive layer having an excellent balance between adhesion to an adherend and durability can be formed. The vinyl monomer having a crosslinkable functional group includes a (meth)acrylic monomer having a crosslinkable functional group and a vinyl monomer other than a (meth)acrylic monomer having a crosslinkable functional group.
[0023] The (meth)acrylic monomer may be (b1) a (meth)acrylic monomer having no crosslinkable functional group, or (b2) a (meth)acrylic monomer having a crosslinkable functional group. These monomers may be used alone or in combination of two or more. The (meth)acrylic monomer having no crosslinkable functional group (b1) is preferably (meth)acrylate monomer having no crosslinkable functional group (b1-1). The (meth)acrylic monomer having a crosslinkable functional group (b2) is preferably (meth)acrylate monomer having a crosslinkable functional group (b2-1).
[0024] The (b1) (meth)acrylic monomer having no crosslinkable functional group may be a (meth)acrylate having a linear alkyl group, a (meth)acrylate having a branched alkyl group, a (meth)acrylate having an alkoxy group, a (meth)acrylate having a polyalkylene glycol structural unit, a (meth)acrylate having an alicyclic hydrocarbon group, a (meth)acrylate having an aromatic group, a (meth)acrylate having a tertiary amino group, or a (meth)acrylamide. Among these, at least one selected from the group consisting of a (meth)acrylate having a linear alkyl group, a (meth)acrylate having a branched alkyl group, a (meth)acrylate having an alicyclic hydrocarbon group, a (meth)acrylate having an aromatic group, or a (meth)acrylamide is preferred.
[0025] The (meth)acrylate having a linear alkyl group is preferably a (meth)acrylate having a linear alkyl group with a carbon number of 1 to 20, and more preferably a (meth)acrylate having a linear alkyl group with a carbon number of 1 to 10. Examples of the (meth)acrylate having a linear alkyl group include (meth)acrylic acid linear alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, n-decyl (meth)acrylate, n-lauryl (meth)acrylate, and n-stearyl (meth)acrylate.
[0026] The (meth)acrylate having a branched alkyl group is preferably a (meth)acrylate having a branched alkyl group having a carbon number of 3 to 20, and more preferably a (meth)acrylate having a branched alkyl group having a carbon number of 3 to 10. Examples of the (meth)acrylate having a branched alkyl group include (meth)acrylic acid branched alkyl esters such as isopropyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, and isodecyl (meth)acrylate.
[0027] Examples of the (meth)acrylate having an alkoxy group include (meth)acrylic acid alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate.
[0028] Examples of the (meth)acrylate having a polyalkylene glycol structural unit include (meth)acrylates having a polyethylene glycol structural unit such as polyethylene glycol (degree of polymerization = 2 to 10) methyl ether (meth)acrylate, polyethylene glycol (degree of polymerization = 2 to 10) ethyl ether (meth)acrylate, polyethylene glycol (degree of polymerization = 2 to 10) propyl ether (meth)acrylate, and polyethylene glycol (degree of polymerization = 2 to 10) phenyl ether (meth)acrylate; and (meth)acrylates having a polypropylene glycol structural unit such as polypropylene glycol (degree of polymerization = 2 to 10) methyl ether (meth)acrylate, polypropylene glycol (degree of polymerization = 2 to 10) ethyl ether (meth)acrylate, polypropylene glycol (degree of polymerization = 2 to 10) propyl ether (meth)acrylate, and polypropylene glycol (degree of polymerization = 2 to 10) phenyl ether (meth)acrylate.
[0029] The (meth)acrylate having an alicyclic hydrocarbon group includes a (meth)acrylate having a cyclic alkyl group and a (meth)acrylate having a polycyclic structure. The (meth)acrylate having a cyclic alkyl group is preferably a (meth)acrylate having a cyclic alkyl group with 6 to 12 carbon atoms. The cyclic alkyl group includes a cyclic alkyl group having a monocyclic structure (e.g., a cycloalkyl group), which may also have a chain portion. Specific examples of the (meth)acrylate having a cyclic alkyl group having a monocyclic structure include (meth)acrylic acid cyclic alkyl esters such as cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, and cyclododecyl (meth)acrylate.
[0030] The (meth)acrylate having a polycyclic structure is preferably a (meth)acrylate having a polycyclic structure with 6 to 12 carbon atoms. Examples of the polycyclic structure include cyclic alkyl groups having a bridged ring structure (e.g., adamantyl group, norbornyl group, isobornyl group), and may also have a chain portion. Specific examples of the (meth)acrylate having a polycyclic structure include bornyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, norbornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, and the like.
[0031] The (meth)acrylate having an aromatic group is preferably a (meth)acrylate having an aromatic group with 6 to 12 carbon atoms. Examples of the aromatic group include an aryl group, and may have a chain portion such as an alkylaryl group, an aralkyl group, and an aryloxyalkyl group. Examples of the (meth)acrylate having an aromatic group include a compound in which an aryl group is directly bonded to a (meth)acryloyloxy group, a compound in which an aralkyl group is directly bonded to a (meth)acryloyloxy group, and a compound in which an alkylaryl group is directly bonded to a (meth)acryloyloxy group. The number of carbon atoms of the aryl group is preferably 6 to 12. The number of carbon atoms of the aralkyl group is preferably 6 to 12. The number of carbon atoms of the alkylaryl group is preferably 6 to 12. Examples of the (meth)acrylate having an aromatic group include benzyl (meth)acrylate, phenyl (meth)acrylate, and phenoxyethyl (meth)acrylate.
[0032] Examples of the (meth)acrylate having a tertiary amino group include 2-(dimethylamino)ethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate.
[0033] Examples of the (meth)acrylamides include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-tert-butyl(meth)acrylamide, N-octyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-ethoxymethyl(meth)acrylamide, N-propoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, diacetone acrylamide, and 4-(meth)acryloylmorpholine. The (meth)acrylamides are (meth)acrylic monomers, but are not included in (meth)acrylate monomers.
[0034] The (b2) (meth)acrylic monomer having a crosslinkable functional group includes a (meth)acrylic monomer having a hydroxy group (preferably a (meth)acrylate monomer), a (meth)acrylic monomer having a carboxy group (preferably (meth)acrylic acid), a (meth)acrylic monomer having an epoxy group (preferably a (meth)acrylate monomer), etc. Among these, a (meth)acrylic monomer having a hydroxy group and / or a (meth)acrylic monomer having a carboxy group are preferred.
[0035] Examples of the (meth)acrylic monomer having a hydroxy group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate; hydroxyalkyl cycloalkane (meth)acrylates such as (4-hydroxymethylcyclohexyl)methyl (meth)acrylate; and caprolactone adducts of hydroxyalkyl (meth)acrylates. Among these, hydroxyalkyl (meth)acrylates are preferred, and (meth)acrylates having a hydroxyalkyl group having 1 to 5 carbon atoms are more preferred.
[0036] Examples of the (meth)acrylic monomer having a carboxy group include monomers obtained by reacting (meth)acrylates having a hydroxy group, such as carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl maleate, and 2-(meth)acryloyloxyethyl phthalate, with acid anhydrides, such as maleic anhydride, succinic anhydride, and phthalic anhydride, and (meth)acrylic acid. Among these, (meth)acrylic acid is preferred.
[0037] Examples of the (meth)acrylic acid ester having an epoxy group include glycidyl (meth)acrylate and 3,4-epoxycyclohexylmethyl (meth)acrylate.
[0038] Examples of the vinyl monomer other than the (meth)acrylic monomer include (b3) a vinyl monomer other than the (meth)acrylic monomer having no crosslinkable functional group, and (b4) a vinyl monomer other than the (meth)acrylic monomer having a crosslinkable functional group. These monomers may be used alone or in combination of two or more kinds.
[0039] Examples of the (b3) vinyl monomer other than the (meth)acrylic monomer having no crosslinkable functional group include aromatic vinyl monomers, vinyl monomers containing a heterocycle, vinyl carboxylate, vinyl monomers containing a tertiary amino group, vinyl monomers containing a quaternary ammonium base, vinyl amides, α-olefins, dienes, and halogenated vinyl monomers.
[0040] Examples of the aromatic vinyl monomer include styrene, α-methylstyrene, 4-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methoxystyrene, 2-hydroxymethylstyrene, and 1-vinylnaphthalene. Examples of the vinyl monomer containing a heterocycle include 2-vinylthiophene, N-methyl-2-vinylpyrrole, 2-vinylpyridine, and 4-vinylpyridine. Examples of the vinyl carboxylate include vinyl acetate, vinyl pivalate, and vinyl benzoate. The vinyl monomer containing a tertiary amino group includes N,N-dimethylallylamine. Examples of the vinyl monomer containing a quaternary ammonium base include N-methacryloylaminoethyl-N,N,N-dimethylbenzyl ammonium chloride. Examples of the vinyl amides include N-vinylformamide, N-vinylacetamide, 1-vinyl-2-pyrrolidone, and N-vinyl-ε-caprolactam. Examples of the α-olefin include 1-hexene, 1-octene, and 1-decene. Examples of the dienes include butadiene, isoprene, 4-methyl-1,4-hexadiene, and 7-methyl-1,6-octadiene. Examples of the halogenated vinyl monomer include vinyl fluoride, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, tetrafluoropropylene, vinylidene chloride, vinyl chloride, 1-chloro-1-fluoroethylene, and 1,2-dichloro-1,2-difluoroethylene.
[0041] Examples of the (b4) vinyl monomer other than the (meth)acrylic monomer having a crosslinkable functional group include vinyl monomers having a hydroxy group, vinyl monomers having a carboxy group, and vinyl monomers containing an epoxy group.
[0042] Examples of the vinyl monomer having a hydroxy group include p-hydroxystyrene and allyl alcohol. Examples of the vinyl monomer having a carboxy group include crotonic acid, maleic acid, itaconic acid, citraconic acid, and cinnamic acid. Examples of the vinyl monomer containing an epoxy group include 2-allyloxirane, glycidyl vinyl ether, and 3,4-epoxycyclohexyl vinyl ether.
[0043] The copolymer (A) may be any one of a random copolymer, a block copolymer, and a graft copolymer, and is preferably a random copolymer.
[0044] The weight average molecular weight (Mw) of the copolymer (A) is preferably 200,000 or more, more preferably 300,000 or more, even more preferably 400,000 or more, and is preferably 2,000,000 or less, more preferably 1,800,000 or less, even more preferably 1,500,000 or less, and particularly preferably 1,100,000 or less. If the Mw of the copolymer (A) is 200,000 or more, the cohesive force is increased and the heat resistance of the adhesive layer is improved, and if it is 2,000,000 or less, the coating workability of the adhesive composition is improved. The method for measuring the weight average molecular weight (Mw) will be described later.
[0045] The molecular weight distribution (PDI) of the copolymer (A) is preferably 3.0 or less, more preferably less than 3.0, even more preferably less than 2.5, even more preferably less than 2.2, and particularly preferably less than 2.0. The smaller the PDI, the narrower the molecular weight distribution width, and the copolymer has a uniform molecular weight, and when the value is 1.0, the molecular weight distribution width is the narrowest. If the PDI is less than 3.0, the content of low molecular weight and high molecular weight is low compared to the molecular weight of the designed copolymer, and an adhesive layer with excellent flex resistance can be obtained. In the present invention, the molecular weight distribution (PDI) is a value calculated by (weight average molecular weight (Mw)) / (number average molecular weight (Mn)), and the measurement method of Mw and Mn will be described later.
[0046] The glass transition temperature (Tg) of the copolymer (A) is preferably −70° C. or higher, more preferably −60° C. or higher, and is preferably 0° C. or lower, more preferably −10° C. or lower, even more preferably −20° C. or lower, and particularly preferably −35° C. or lower. If the glass transition temperature is −70° C. or higher, sufficient cohesive force is imparted to the adhesive layer, improving the durability of the adhesive layer, and if the glass transition temperature is 0° C. or lower, the adhesive layer has high adhesion to the adherend, peeling and the like is suppressed, improving durability.
[0047] The glass transition temperature (Tg) of the copolymer (A) is a value calculated by the following FOX formula (Formula (1)). In Formula (1), Tg represents the glass transition temperature (°C) of the copolymer. Tgi represents the glass transition temperature (°C) when vinyl monomer i forms a homopolymer. Wi represents the mass ratio of vinyl monomer i to all vinyl monomers forming the copolymer, and ΣWi=1. i is a natural number from 1 to n.
[0048]
number
[0049] Table 1 shows the glass transition temperatures of representative homopolymers.
[0050] [Table 1]
[0051] (A) Method for Producing (Meth)acrylic Acid-Based Copolymer) The (A) copolymer can be produced by radical polymerization of a monomer composition containing two or more kinds of vinyl monomers, and is preferably obtained by living radical polymerization (obtained by polymerization using a living radical polymerization method).
[0052] Living radical polymerization method maintains the simplicity and versatility of conventional radical polymerization method, while being less susceptible to termination reaction and chain transfer, and grows without being hindered by side reactions that deactivate the growing end, so that it is easy to precisely control the molecular weight distribution and produce a polymer with a uniform composition. Therefore, in the copolymer produced by living radical polymerization method, crosslinkable functional groups are uniformly distributed in each molecular chain. Therefore, if the copolymer produced by living radical polymerization method is used, the crosslinking point density in the adhesive layer formed is uniform as a whole. If the crosslinking point density is uniform as a whole, the restoration rate of the adhesive layer can be improved.
[0053] In the living radical polymerization method, a mixture of the monomers (vinyl monomers) constituting the copolymer (A) can be used to obtain a random copolymer, or the vinyl monomers constituting the copolymer can be reacted sequentially to obtain a block copolymer.
[0054] Living radical polymerization methods include, depending on the method of stabilizing the polymer growing end, a method using a transition metal catalyst (ATRP method), a method using a sulfur-based reversible chain transfer agent (RAFT method), a method using an organic tellurium compound (TERP method), etc. Among these methods, the TERP method is preferred from the viewpoints of the variety of monomers that can be used, molecular weight control in the polymer region, uniform composition, and coloring.
[0055] The TERP method is a method in which an organic tellurium compound is used as a chain transfer agent to polymerize a radically polymerizable compound (vinyl monomer), and is a method described, for example, in WO 2004 / 14848, WO 2004 / 14962, WO 2004 / 072126, and WO 2004 / 096870.
[0056] Specific polymerization methods of the TERP method include the following (a) to (d). (a) A method of polymerizing a vinyl monomer using an organotellurium compound represented by formula (1). (b) A method of polymerizing a vinyl monomer using a mixture of an organotellurium compound represented by formula (1) and an azo-based polymerization initiator. (c) A method of polymerizing a vinyl monomer using a mixture of an organotellurium compound represented by formula (1) and an organoditelluride compound represented by formula (2). (d) A method of polymerizing a vinyl monomer using a mixture of an organotellurium compound represented by formula (1), an azo-based polymerization initiator, and an organic ditelluride compound represented by formula (2).
[0057] [ka] [In formula (1), R1 R is an alkyl group having 1 to 8 carbon atoms, an aryl group, or an aromatic heterocyclic group. 2 and R 3 are each independently a hydrogen atom or an alkyl group having 1 to 8 carbon atoms. 4 is an alkyl group having 1 to 8 carbon atoms, an aryl group, a substituted aryl group, an aromatic heterocyclic group, an alkoxy group, an acyl group, an amido group, an oxycarbonyl group, a cyano group, an allyl group, or a propargyl group. In formula (2), R 1 is an alkyl group having 1 to 8 carbon atoms, an aryl group, or an aromatic heterocyclic group.]
[0058] Specific examples of the organic tellurium compound represented by formula (1) include ethyl-2-methyl-2-n-butyltellanyl-propionate, ethyl-2-n-butyltellanyl-propionate, (2-hydroxyethyl)-2-methyl-methyltellanyl-propionate, and the organic tellurium compounds described in WO 2004 / 14848, WO 2004 / 14962, WO 2004 / 072126, and WO 2004 / 096870. Specific examples of the organic ditelluride compound represented by formula (2) include dimethyl ditelluride, dibutyl ditelluride, and the like. The azo polymerization initiator can be any azo polymerization initiator used in normal radical polymerization without any particular limitation. Examples of the azo polymerization initiator include 2,2'-azobis(isobutyronitrile) (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile) (ADVN), 1,1'-azobis(1-cyclohexanecarbonitrile) (ACHN), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (V-70), and the like.
[0059] In the polymerization step, a vinyl monomer and an organic tellurium compound of formula (1) are mixed in a vessel purged with an inert gas, and for the purpose of promoting the reaction and controlling the molecular weight and molecular weight distribution according to the type of vinyl monomer, an azo-based polymerization initiator and / or an organic ditelluride compound of formula (2) are further mixed. Examples of the inert gas include nitrogen, argon, and helium. Argon and nitrogen are preferable. The amount of the vinyl monomer used in the above (a), (b), (c), and (d) may be appropriately adjusted depending on the physical properties of the desired copolymer.
[0060] The polymerization reaction can be carried out without a solvent, but may be carried out by stirring the mixture using an aprotic solvent or a protic solvent generally used in radical polymerization. Examples of aprotic solvents that can be used include anisole, benzene, toluene, propylene glycol monomethyl ether acetate, ethyl acetate, and tetrahydrofuran (THF). Examples of protic solvents include water, methanol, and 1-methoxy-2-propanol. The solvent may be used alone or in combination of two or more. The amount of the solvent used may be appropriately adjusted, and is preferably 0.01 ml to 50 ml per 1 g of vinyl monomer. The reaction temperature and reaction time may be appropriately adjusted depending on the molecular weight or molecular weight distribution of the resulting copolymer, but the mixture is usually stirred at 0°C to 150°C for 1 minute to 100 hours. After the polymerization reaction is completed, the solvent used and the remaining vinyl monomer are removed from the resulting reaction mixture by a conventional separation and purification means, and the target copolymer can be separated.
[0061] The growing end of the copolymer obtained by the polymerization reaction is -TeR derived from the tellurium compound. 1 (In the formula, R 1is the same as above), and is deactivated by handling in air after the polymerization reaction is completed, but tellurium atoms may remain. Since copolymers with tellurium atoms remaining at the terminals are colored and have poor thermal stability, it is preferable to remove the tellurium atoms. Methods for removing tellurium atoms include radical reduction methods, adsorption methods using activated carbon, and adsorption of metals using ion exchange resins, and these methods can also be used in combination. The other end of the copolymer obtained by the polymerization reaction (the end opposite to the growing end) is formed of -CR derived from the tellurium compound. 2 R 3 R 4 (In the formula, R 2 , R 3 and R 4 is R in formula (1). 2 , R 3 and R 4 (same as above.)
[0062] ((B) Crosslinking Agent) The adhesive composition contains a crosslinking agent (B). The crosslinking agent (B) is a compound having two or more crosslinkable points in one molecule that can crosslink with a functional group (preferably the crosslinkable functional group) of the copolymer (A). The crosslinkable points are reactive groups that can react with a functional group of the copolymer (A), or metal atoms that can react with a functional group of the copolymer (A). In a metal chelate compound, the number of crosslinkable points is the valence of a central metal atom. In a metal chelate compound, even if an alkoxy group is bonded to the central metal, the number of crosslinkable points is the valence of the central metal. In a metal alkoxide compound, a metal acylate compound, an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, and an aziridine-based crosslinking agent, the number of crosslinkable points is the number of alkoxy groups, acylate groups, isocyanate groups, epoxy groups, or aziridine groups.
[0063] The adhesive composition contains an organometallic compound as a crosslinking agent (B). Examples of the organometallic compound include metal chelate compounds, metal acylate compounds, and metal alkoxide compounds. From the viewpoint of reactivity with the crosslinkable functional group of the copolymer (A), metal chelate compounds or metal alkoxide compounds are preferred. From the viewpoint of the adhesive strength and recovery of the adhesive layer with the adherend, the organometallic compound is more preferably a metal chelate compound. The organometallic compounds may be used alone or in combination of two or more kinds.
[0064] (Metal chelate compounds) A metal chelate compound is a compound in which one or more polydentate ligands are bonded to a central metal atom. An adhesive material made of an adhesive composition containing a metal chelate compound has a crosslinked structure due to complex bond crosslinking, and is crosslinked by a weak bond compared to a covalent bond, so it is presumed to have high stress relaxation even if the number of crosslinking points is relatively large, and excellent recovery can be obtained while maintaining adhesive strength with an adherend. The metal chelate compound may be used alone or in combination of two or more types.
[0065] The metal chelate compound has the general formula M(L): m (X) n (Z) q (wherein, M represents a metal atom, L represents a polydentate ligand, X represents a monodentate ligand, Z represents an alkoxy group, m represents an integer of 1 or more, n represents an integer of 0 or more, and q represents an integer of 0 or more. When m is 2 or more, m Ls may be the same ligand or different ligands. When n is 2 or more, n Xs may be the same ligand or different ligands. When q is 2 or more, q Zs may be the same ligand or different ligands.) is preferred. The coordination number of the metal atom is 3 to 20, preferably 4 to 16.
[0066] Examples of the metal atom represented by M in the metal chelate compound include aluminum, zinc, titanium, zirconium, iron, nickel, manganese, chromium, vanadium, and tin, with aluminum, titanium, and zirconium being preferred.
[0067] The metal chelate compound preferably has only a polydentate ligand as a ligand. Examples of the polydentate ligand represented by L include acetylacetonate-based ligands, acetoacetate-based ligands, acetoacetate-based ligands, lactate-based ligands, carboxylic acid-based ligands, citrate-based ligands, and glycol-based ligands. Specific examples include acetylacetonate, alkylacetoacetate, alkylenediamine tetraacetate, diisoalkoxybisalkylacetoacetate, diisopropoxybisalkylacetoacetate, dialkoxy-bisalkyl-acetoacetate, and hydroxyalkylenediamine triacetate. The metal chelate compound preferably has an acetylacetonate-based ligand as a ligand, and more preferably has acetylacetonate.
[0068] Examples of aluminum chelate compounds include diisopropoxyaluminum monooleyl acetoacetate, monoisopropoxyaluminum bisoleyl acetoacetate, monoisopropoxyaluminum monooleate monoethyl acetoacetate, diisopropoxyaluminum monolauryl acetoacetate, diisopropoxyaluminum monostearyl acetoacetate, diisopropoxyaluminum monoisostearyl acetoacetate, monoisopropoxyaluminum mono-N-lauroyl-β-alanate monolauryl acetoacetate, aluminum tris(acetylacetonate), monoacetylacetonate aluminum bis(isobutyl acetoacetate) chelate, monoacetylacetonate aluminum bis(2-ethylhexyl acetoacetate) chelate, monoacetylacetonate aluminum bis(dodecyl acetoacetate) chelate, monoacetylacetonate aluminum bis(oleyl acetoacetate) chelate, etc. Among these, aluminum tris(acetylacetonate) is preferred from the viewpoint of the above-mentioned effects.
[0069] Examples of titanium chelate compounds include diisopropoxybis(ethylacetoacetate)titanium, diisopropoxybis(acetylacetonate)titanium, and diisopropoxybis(acetylacetonate)titanium.
[0070] Examples of zirconium chelate compounds include tributoxyacetylacetonate zirconium, tributoxyethylacetoacetate zirconium, dibutoxybis(ethylacetoacetate) zirconium, butoxytris(ethylacetoacetate) zirconium, tetrakis(propylacetoacetate) zirconium, tetrakis(acetylacetonate) zirconium, and tetrakis(ethylacetoacetate) zirconium.
[0071] (Metal alkoxide compounds) The metal alkoxide compound has the general formula R 11 n M(OR12 ) m (In the formula, R 11 , R 12 represents an alkyl group having 1 to 8 carbon atoms, and different R 11 , R 12 may be present in one molecule, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M. The metal alkoxide compounds may be used alone or in combination of two or more. may be also possible.
[0072] Examples of the metal atom represented by M in the metal alkoxide include silicon, aluminum, titanium, zirconium, etc. Examples of the metal alkoxide include aluminum alkoxides such as aluminum isopropylate, aluminum butylate, and aluminum ethylate; titanium alkoxides such as isopropyl titanate, normal butyl titanate, butyl titanate dimer, tetraoctyl titanate, tertiary amyl titanate, tertiary butyl titanate, and tetrastearyl titanate; and zirconium alkoxides such as normal propyl zirconate and normal butyl zirconate.
[0073] (Metal acylate compounds) The metal acylate compound is a compound in which at least one alkylcarbonyloxy group (-OCOR (R is an alkyl group)) is bonded to a metal. Examples of the alkylcarbonyloxy group include a heptylcarbonyloxy group, an octylcarbonyloxy group, a heptadecylcarbonyloxy group, and an octadecylcarbonyloxy group. The metal acylate compound may be used alone or in combination of two or more kinds.
[0074] Examples of metal atoms constituting the metal acylate include titanium, zirconium, etc. Examples of the metal acylate include tributoxytitanium monostearate, diisopropoxytitanium distearate, titanium stearate, titanium isostearate, zirconium stearate, etc.
[0075] The adhesive composition may contain only an organometallic compound as the crosslinking agent (B), or may contain a crosslinking agent other than the organometallic compound.
[0076] Examples of the crosslinking agent other than the organometallic compound include an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, an aziridine-based crosslinking agent, a melamine resin-based crosslinking agent, a urea resin-based crosslinking agent, etc. Among these, an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, and an aziridine-based crosslinking agent are preferred, and an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent are more preferred from the viewpoint of ease of controlling the degree of progress of the crosslinking reaction and bending resistance, and an epoxy-based crosslinking agent is particularly preferred from the viewpoint of heat resistance.
[0077] (Isocyanate-based crosslinking agent) The isocyanate crosslinking agent is a compound having two or more isocyanate groups (including isocyanate regenerating functional groups in which the isocyanate groups are temporarily protected by a blocking agent or oligomerization) in one molecule as reactive groups. The isocyanate crosslinking agents may be used alone or in combination of two or more kinds.
[0078] Examples of the isocyanate-based crosslinking agent include aromatic polyisocyanates, alicyclic polyisocyanates, aliphatic polyisocyanates, as well as adducts of these with various polyols, and polyisocyanates which have been multifunctionalized with isocyanurate bonds, biuret bonds, allophanate bonds, or the like. More specifically, for example, lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic polyisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, hydrogenated tolylene diisocyanate, and 1,3-bis(isocyanatomethyl)cyclohexane; 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate, tetramethylxylylene diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, polymethylene One or more selected from aromatic polyisocyanates such as polyphenyl isocyanate; isocyanate adducts such as trimethylolpropane / tolylene diisocyanate trimer adduct, trimethylolpropane / hexamethylene diisocyanate trimer adduct, and isocyanurate of hexamethylene diisocyanate; trimethylolpropane adduct of xylylene diisocyanate; trimethylolpropane adduct of hexamethylene diisocyanate; polyether polyisocyanate, polyester polyisocyanate, and adducts of these with various polyols, polyisocyanates multifunctionalized with isocyanurate bonds, biuret bonds, allophanate bonds, etc. can be used. Among these, it is preferable to use an aliphatic polyisocyanate, and an isocyanurate of an aliphatic diisocyanate (for example, an isocyanurate of hexamethylene diisocyanate) is more preferable.
[0079] (Epoxy crosslinking agent) The epoxy crosslinking agent is a compound having two or more epoxy groups as reactive groups in one molecule. The epoxy crosslinking agent may be used alone or in combination of two or more kinds.
[0080] Examples of epoxy crosslinking agents include bisphenol A, epichlorohydrin type epoxy resins, ethylene glycidyl ether, N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, diamine glycidylamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, glycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, and the like.
[0081] The content of the crosslinkable points of the (B) crosslinking agent is preferably 0.5 mmol / g or more, more preferably 1.0 mmol / g or more, even more preferably 3.0 mmol / g or more, particularly preferably 6.0 mmol / g or more, and is preferably 20 mmol / g or less, more preferably 15.0 mmol / g or less, even more preferably 12.0 mmol / g or less. If the content of the crosslinkable points of the (B) crosslinking agent is within this range, the cohesive strength of the adhesive layer formed becomes favorable, and even if the adhesive layer is bent, the occurrence of deformation at the bent portion can be further suppressed.
[0082] The total amount of crosslinkable points possessed by the (B) crosslinking agent relative to the unit mass of the (A) copolymer in the adhesive composition is preferably 7 μmol / g or more, more preferably 10 μmol / g or more, even more preferably 15 μmol / g or more, particularly preferably 20 μmol / g or more, and is preferably 60 μmol / g or less, more preferably 50 μmol / g or less, and even more preferably 40 μmol / g or less. If the total amount of crosslinkable points possessed by the (B) crosslinking agent is 7 μmol / g or more, sufficient cohesive strength is exerted, and the adhesive layer formed exhibits excellent flexibility, and if it is 60 μmol / g or less, the adhesive layer has improved adhesion to the substrate, and peeling during bending is suppressed.
[0083] In the pressure-sensitive adhesive composition, the molar ratio of the crosslinkable functional groups of the (A) copolymer to the total amount of crosslinkable points of the (B) crosslinking agent (molar amount of crosslinkable functional groups / molar amount of crosslinkable points) is preferably 1 or more, more preferably 2 or more, even more preferably 10 or more, and is preferably 1000 or less, more preferably 200 or less, even more preferably 100 or less, and particularly preferably 50 or less.
[0084] The ratio of the organometallic compound in the (B) crosslinking agent is 65 mol% or more, preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and particularly preferably 100 mol% based on the total 100 mol% of the crosslinkable points of the crosslinking agent. If the ratio of the crosslinkable points of the organometallic compound is 65 mol% or more, the adhesive strength and restoring force of the resulting adhesive layer can be achieved at the same time.
[0085] (Other additives) In addition to the (A) copolymer and (B) crosslinking agent, other additives may be added to the adhesive composition. Examples of other additives include crosslinking accelerators, crosslinking retarders, tackifier resins, plasticizers, softeners, peeling aids, silane coupling agents, dyes, pigments, dyes, fluorescent brighteners, antistatic agents, wetting agents, surfactants, thickeners, antifungal agents, preservatives, oxygen absorbers, ultraviolet absorbers, antioxidants, near-infrared absorbers, water-soluble quenchers, fragrances, metal deactivators, nucleating agents, alkylating agents, flame retardants, lubricants, processing aids, etc. These are appropriately selected and mixed according to the application and purpose of the adhesive.
[0086] (Crosslinking retarder) The adhesive composition may be used by blending a crosslinking retarder as necessary. The crosslinking retarder is a compound capable of suppressing excessive viscosity increase of an adhesive composition containing a crosslinking agent by blocking a functional group of the crosslinking agent. The type of crosslinking retarder is not particularly limited, but may be, for example, β-diketones such as acetylacetone, hexane-2,4-dione, heptane-2,4-dione, and octane-2,4-dione; β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, propyl acetoacetate, butyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate; and benzoylacetone. The crosslinking retarder is preferably one that can act as a chelating agent, and is preferably β-diketones or β-ketoesters, and particularly preferably acetylacetone.
[0087] The content of the crosslinking retarder that can be blended in the adhesive composition is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, even more preferably 0.08 parts by mass or more, and is preferably 4.0 parts by mass or less, more preferably 3.0 parts by mass or less, even more preferably 1.0 parts by mass or less, relative to 100 parts by mass of the (A) copolymer. By adjusting the content of the crosslinking retarder within the above range, it is possible to suppress excessive viscosity increase and gelation of the adhesive composition after blending the (B) crosslinking agent in the adhesive composition, and to extend the storage stability (pot life) of the adhesive composition.
[0088] When a β-ketoester is used as the crosslinking retarder, the mass ratio of the organometallic compound to the crosslinking retarder (organometallic compound / crosslinking retarder) is preferably 0.25 or more, more preferably 0.43 or more, and even more preferably 0.67 or more, and is preferably 4.0 or less, more preferably 2.3 or less, and even more preferably 1.5 or less.
[0089] (Silane coupling agent) The adhesive composition may be used by blending a silane coupling agent as necessary. The silane coupling agent is not particularly limited, but may be, for example, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane or other epoxy group-containing silane coupling agents; 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylidene)propylamine, N-phenyl-γ-aminopropyltrimethoxysilane or other amino group-containing silane coupling agents; 3-acryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane or other (meth)acryl group-containing silane coupling agents; 3-isocyanatepropyltriethoxysilane or other isocyanate group-containing silane coupling agents.
[0090] The content of the silane coupling agent that can be blended in the adhesive composition is preferably 1 part by mass or less, more preferably 0.01 to 1 part by mass, and even more preferably 0.02 to 0.6 parts by mass, based on 100 parts by mass of the (A) copolymer. By adjusting the content of the silane coupling agent within the above range, it is possible to increase the water resistance at the interface when the adhesive layer is applied to a hydrophilic adherend such as glass.
[0091] (tackifier resin) The pressure-sensitive adhesive composition may be used by blending a tackifier resin other than the copolymer (A) as necessary. The tackifier resin is not particularly limited, but examples thereof include rosin-based tackifier resins, terpene-based tackifier resins, phenol-based tackifier resins, and hydrocarbon-based tackifier resins.
[0092] Examples of rosin-based tackifying resins include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins obtained by modifying these unmodified rosins through polymerization, disproportionation, hydrogenation, or the like (polymerized rosin, stabilized rosin, disproportionated rosin, fully hydrogenated rosin, partially hydrogenated rosin, other chemically modified rosins, and the like); and various rosin derivatives.
[0093] Examples of the rosin derivatives include rosin phenol-based resins obtained by adding phenol to rosins (unmodified rosin, modified rosin) using an acid catalyst and thermally polymerizing the resulting mixture; rosin ester-based resins such as rosin ester compounds (unmodified rosin esters) obtained by esterifying unmodified rosin with alcohols, and modified rosin ester compounds (polymerized rosin ester, stabilized rosin ester, disproportionated rosin ester, fully hydrogenated rosin ester, partially hydrogenated rosin ester, etc.) obtained by esterifying modified rosin with alcohols; unsaturated fatty acid modified rosin-based resins obtained by modifying unmodified rosin or modified rosin with unsaturated fatty acid; unsaturated fatty acid modified rosin ester-based resins obtained by modifying rosin ester-based resins with unsaturated fatty acid; rosin alcohol-based resins obtained by reducing the carboxyl groups in unmodified rosin, modified rosin, unsaturated fatty acid modified rosin resins, and unsaturated fatty acid modified rosin ester-based resins; and metal salts of rosin-based resins such as unmodified rosin and modified rosin (particularly rosin ester-based resins).
[0094] Examples of terpene-based tackifying resins include terpene-based resins such as α-pinene polymers, β-pinene polymers, and dipentene polymers, and modified terpene-based resins obtained by modifying these terpene-based resins (phenol-modified, aromatic-modified, hydrogen-modified, hydrocarbon-modified, etc.) (e.g., terpene-phenolic resins, styrene-modified terpene resins, aromatic-modified terpene resins, and hydrogenated terpene resins).
[0095] Examples of phenol-based tackifying resins include condensates of various phenols (e.g., phenol, m-cresol, 3,5-xylenol, p-alkylphenol, resorcinol) with formaldehyde (e.g., alkylphenol-based resins, xylene formaldehyde-based resins), resols obtained by addition reaction of the phenols with formaldehyde using an alkali catalyst, and novolaks obtained by condensation reaction of the phenols with formaldehyde using an acid catalyst.
[0096] Examples of hydrocarbon-based tackifying resins (petroleum-based tackifying resins) include aliphatic hydrocarbon resins [polymers of aliphatic hydrocarbons such as olefins and dienes having 4 to 5 carbon atoms (olefins such as butene-1, isobutylene, and pentene-1; dienes such as butadiene, 1,3-pentadiene, and isoprene)], aliphatic cyclic hydrocarbon resins [alicyclic hydrocarbon resins obtained by cyclizing and dimerizing so-called "C4 petroleum fractions" and "C5 petroleum fractions" and then polymerizing them, cyclic diene compounds (cyclopentadiene, dicyclopentadiene, ethylidene norbornene, dicyclopentadiene ... Examples of such resins include polymers of vinyl groups having 8 to 10 carbon atoms (styrene, vinyltoluene, α-methylstyrene, indene, methylindene, etc.) or their hydrogenated products, alicyclic hydrocarbon resins obtained by hydrogenating the aromatic rings of the aromatic hydrocarbon resins or aliphatic or aromatic petroleum resins described below], aromatic hydrocarbon resins [polymers of vinyl group-containing aromatic hydrocarbons having 8 to 10 carbon atoms (styrene, vinyltoluene, α-methylstyrene, indene, methylindene, etc.)], aliphatic or aromatic petroleum resins (styrene-olefin copolymers, etc.), aliphatic or alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, and coumarone-indene resins.
[0097] The content of the tackifier resin that can be blended in the adhesive composition is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, even more preferably 20 parts by mass or more, and preferably 60 parts by mass or less, more preferably 50 parts by mass or less, even more preferably 40 parts by mass or less, relative to 100 parts by mass of the (A) copolymer. By adjusting the content of the tackifier resin within the above range, the adhesive layer formed can ensure sufficient adhesion to the adherend, and peeling during bending can be suppressed.
[0098] (Method of manufacturing adhesive composition) The adhesive composition can be produced by mixing the copolymer (A), the crosslinking agent (B), and other additives used as necessary. The adhesive composition may contain a solvent derived from the production of the copolymer (A), or may be a solution diluted with an appropriate solvent to have a viscosity suitable for forming an adhesive layer.
[0099] Examples of the solvent include aliphatic hydrocarbons such as hexane and heptane, aromatic hydrocarbons such as toluene and xylene, halogenated hydrocarbons such as methylene chloride and ethylene chloride, ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, 2-pentanone, isophorone, and cyclohexanone, esters such as ethyl acetate, propyl acetate, isopropyl acetate, and butyl acetate, cellosolve-based solvents such as ethyl cellosolve, and alcohol-based solvents such as ethanol, isopropyl alcohol, n-butyl alcohol, ethylene glycol monomethyl ether, ethylene glycol monoisopropyl ether, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether. These solvents may be used alone or in combination of two or more.
[0100] The amount of the solvent used is not particularly limited and may be appropriately adjusted so that the adhesive composition has a viscosity suitable for coating. From the viewpoint of coatability, the amount is, for example, preferably 1% by mass to 90% by mass, more preferably 10% by mass to 80% by mass, and even more preferably 20% by mass to 70% by mass.
[0101] (Applications of adhesive composition) The adhesive composition is preferably used for forming a flexible display that can be repeatedly bent and used, or an adhesive layer used in a flexible display.
[0102] Examples of the flexible display that can be repeatedly bent and stretched include a foldable display that can be folded, a rollable display that can be rolled into a cylindrical shape, etc. Flexible displays are expected to be used in mobile terminals such as smartphones and tablet terminals, and stationary displays that can be stored, etc.
[0103] [Adhesive for flexible displays] The adhesive material of the present invention is characterized by being obtained by curing the adhesive composition for a flexible display. The adhesive material for a flexible display can be an adhesive layer used for bonding one flexible member to another flexible member in a flexible display.
[0104] The gel fraction of the adhesive is preferably 20% to 100%, more preferably 50% to 100%, and particularly preferably 70% to 100%, from the viewpoint of durability and adhesive strength. If the gel fraction is too low, the adhesive is likely to have insufficient durability due to insufficient cohesive strength. The gel fraction can be controlled by the amount of crosslinking agent in the adhesive composition, the crosslinking temperature, and the crosslinking time.
[0105] The glass transition temperature (Tg) of the adhesive is preferably -70°C or higher, more preferably -60°C or higher, even more preferably -50°C or higher, and is preferably 0°C or lower, more preferably -10°C or lower, even more preferably -20°C or lower, and particularly preferably -35°C or lower. If the glass transition temperature is -70°C or higher, the adhesive is given sufficient cohesive force and the durability of the adhesive is improved, and if the glass transition temperature is 0°C or lower, the adhesive has high adhesion to the adherend, peeling is suppressed, and durability is improved. In addition, the adhesive can withstand repeated bending in low temperature environments such as cold regions. The method for measuring the glass transition temperature (Tg) of the adhesive will be described later.
[0106] The shear storage modulus (G') of the adhesive at 25° C. is preferably 0.015 MPa or more, more preferably 0.02 MPa or more, and even more preferably 0.025 MPa or more, and is preferably 0.07 MPa or less, more preferably 0.05 MPa or less, and even more preferably 0.04 MPa or less.
[0107] The shear storage modulus (G') of the adhesive at -40°C is preferably 0.1 MPa or more, more preferably 0.2 MPa or more, even more preferably 0.4 MPa or more, and is preferably 1.8 MPa or less, more preferably 1.5 MPa or less, even more preferably 1.2 MPa or less.
[0108] The shear storage modulus (G') of the adhesive at 60° C. is preferably 0.01 MPa or more, more preferably 0.02 MPa or more, even more preferably 0.03 MPa or more, and is preferably 0.06 MPa or less, more preferably 0.055 MPa or less, even more preferably 0.05 MPa or less.
[0109] When the shear storage modulus (G') of the adhesive at 25°C, -40°C, and 60°C is within the above range, the adhesive has appropriate flexibility even in high and low temperature environments, has better shape conformability, and has better cohesive strength and adhesiveness. The method for measuring the shear storage modulus (G') of the adhesive will be described later.
[0110] The higher the recovery rate when the adhesive is distorted by 400%, the more preferable, and it is 75% or more, more preferably 80% or more, even more preferably 83% or more, and particularly preferably 85% or more, with the upper limit being 100%. If the recovery rate is 75% or more, the deformation that occurs when the flexible laminated member is left in a bent state for a long period of time and then stretched is easily restored to its original state, so that the occurrence of poor appearance such as waviness at the bent portion can be suppressed.
[0111] The stress 10 minutes after the adhesive material is distorted by 400% is preferably 0.04 MPa or less from the viewpoint of relaxation of the stress applied when the adhesive material is bent and stretched. More preferably, it is 0.035 MPa or less, and even more preferably, it is 0.03 MPa or less. Furthermore, from the viewpoint of ease of obtaining the recovery rate, it is preferably 0.007 MPa or more. More preferably, it is 0.01 MPa or more, and even more preferably, it is 0.013 MPa or more. The method of measuring the recovery rate and stress of the adhesive material will be described later.
[0112] [Adhesive sheets for flexible displays] The adhesive sheet for flexible displays of the present invention has an adhesive layer used for bonding one flexible member to another flexible member, and a flexible sheet member attached to at least one side of the adhesive layer, and is characterized in that the adhesive layer is formed from the adhesive material for flexible displays.
[0113] The configuration of the adhesive sheet can be exemplified by an embodiment having an adhesive layer and a first flexible sheet member attached to one side of the adhesive layer; or an embodiment having an adhesive layer, a first flexible sheet member attached to one side of the adhesive layer, and a second flexible sheet member attached to the other side of the adhesive layer.
[0114] An example of the adhesive sheet of the present invention is shown in Figure 1. The adhesive sheet 10 in Figure 1 is composed of an adhesive layer 12, and a first flexible sheet member 14 and a second flexible sheet member 16 that sandwich the adhesive layer 12. The adhesive layer 12 is in contact with the releasable surfaces of the first flexible sheet member 14 and the second flexible sheet member 16.
[0115] (Adhesive layer) The thickness of the adhesive layer is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, and particularly preferably 40 μm or more. If the thickness is 5 μm or more, sufficient adhesion to the flexible sheet member can be obtained. In addition, the thickness of the adhesive layer is preferably 100 μm or less, more preferably 75 μm or less, and even more preferably 60 μm or less. If the thickness is 100 μm or less, protrusion of the adhesive layer can be suppressed.
[0116] The adhesive strength of the adhesive layer to the flexible sheet member (excluding the release sheet) at 23°C is preferably 10 N / 25 mm or more, more preferably 12 N / 25 mm or more, and even more preferably 15 N / 25 mm or more. If it is 10 N / 25 mm or more, lifting or peeling of the adhesive material can be suppressed. There is no particular upper limit to the adhesive strength, but it is usually 50 N / 25 mm or less, preferably 40 N / 25 mm or less.
[0117] The adhesive strength of the adhesive layer to the flexible sheet member (excluding the release sheet) at 60°C is preferably 8N / 25mm or more, more preferably 10N / 25mm or more, and even more preferably 12N / 25mm or more. If it is 8N / 25mm or more, lifting or peeling of the adhesive material can be suppressed even in a high temperature environment. There is no particular upper limit for the adhesive strength, but it is usually 50N / 25mm or less, preferably 40N / 25mm or less.
[0118] (Flexible sheet member) The flexible sheet member may include a base sheet having flexibility, a release sheet, etc. The base sheet is a sheet member supporting the adhesive layer, and this sheet member may be a functional sheet member. The functional sheet member may include a cover film, a barrier film, a polarizing film, a retardation film, an optical compensation film, a brightness improvement film, a diffusion film, an anti-reflection film, etc. The release sheet protects the adhesive layer until the adhesive layer is attached to the adherend, and is peeled off from the adhesive layer before the adhesive layer is attached to the adherend.
[0119] Generally, a "sheet" is defined in JIS as a thin, flat product whose thickness is generally small relative to its length and width, and a "film" is generally a thin, flat product whose thickness is extremely small compared to its length and width, and whose maximum thickness is arbitrarily limited, and which is usually supplied in the form of a roll (Japanese Industrial Standard JIS K6900). For example, in terms of thickness, in the narrow sense, a product with a thickness of 100 μm or more is called a sheet, and a product with a thickness of less than 100 μm is sometimes called a film. However, the boundary between a sheet and a film is unclear, and since there is no need to distinguish between the two in the present invention, in the present invention, when a product is called a "sheet," it is also considered to include a "film," and when a product is called a "film," it is also considered to include a "sheet."
[0120] The flexible sheet member may be a sheet of a polymer material, a glass sheet, etc. The thickness of the flexible sheet member is not particularly limited, but from the viewpoint of excellent handleability, etc., it is preferably 2 μm to 500 μm, more preferably 2 μm to 200 μm.
[0121] Examples of the polymeric materials include polyester resins such as polyethylene terephthalate resin and polyethylene naphthalate resin; polycarbonate resin; poly(meth)acrylate resin; polystyrene resin; polyamide resin; polyimide resin; polyacrylonitrile resin; polyolefin resins such as polypropylene resin, polyethylene resin, polycycloolefin resin, and cycloolefin copolymer resin; cellulose-based resins such as triacetyl cellulose resin and diacetyl cellulose resin; polyphenylene sulfide resin; polyvinyl chloride resin; polyvinylidene chloride resin; polyvinyl alcohol resin, and the like.
[0122] The flexible sheet member may be composed of a single layer containing one or more of the polymeric materials, or may be composed of two or more layers, such as a layer containing one or more of the polymeric materials and a layer containing one or more of a polymeric material different from the layer containing one or more of the polymeric materials.
[0123] The flexible sheet member is preferably a release sheet having a surface in contact with the adhesive layer that has been subjected to a release treatment. Examples of the release agent used in the release treatment include silicone-based, fluorine-based, alkyd-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents.
[0124] The adhesive sheet has a first flexible sheet member attached to one side of the adhesive layer and a second flexible sheet member attached to the other side of the adhesive layer, the first flexible sheet member being a first release sheet, the second flexible sheet member being a second release sheet, and the first release sheet and the second release sheet are preferably attached so that their respective release surfaces are in contact with the adhesive layer. When the adhesive layer is sandwiched between two release sheets, it is preferable that one release sheet is a heavy release type release sheet with a large release force, and the other release sheet is a light release type release sheet with a small release force.
[0125] (Manufacturing of adhesive sheets) The pressure-sensitive adhesive sheet can be produced, for example, by applying the above-mentioned pressure-sensitive adhesive composition onto a flexible sheet member and, if necessary, curing the composition by a dry heat treatment to form a pressure-sensitive adhesive layer.
[0126] The adhesive composition can be applied by various coating methods such as reverse gravure coating, direct gravure coating, die coating, bar coating, wire bar coating, roll coating, spin coating, dip coating, spray coating, knife coating, kiss coating, etc., or various printing methods such as inkjet printing, offset printing, screen printing, flexographic printing, etc. In addition, before applying the adhesive composition, the surface of the release sheet may be subjected to a surface treatment such as corona treatment, plasma treatment, hot air treatment, ozone treatment, ultraviolet treatment, etc.
[0127] The drying and curing process is not particularly limited as long as it can remove the solvent used in the adhesive composition and can cure the adhesive composition, but it is preferable to perform the drying and curing process at a temperature of 60° C. to 150° C. for about 20 to 300 seconds. In particular, the drying temperature is preferably 100° C. to 130° C.
[0128] When the first flexible sheet member is disposed on one side of the adhesive layer and the second flexible sheet member is disposed on the other side, the adhesive composition is applied to the first flexible sheet member, an adhesive layer is formed on the first flexible sheet member, and then the second flexible sheet member is attached to the adhesive layer. Furthermore, the adhesive layer may be cured as necessary. The curing conditions include, for example, 40°C for about 3 to 7 days.
[0129] [Flexible laminated member] The flexible laminated member of the present invention is a flexible laminated member including a first flexible member, a second flexible member, and an adhesive layer that bonds the first flexible member and the second flexible member to each other, and is characterized in that the adhesive layer is formed from the adhesive. Since the adhesive layer of the flexible laminated member is an adhesive formed from the adhesive composition, even when the flexible laminated member is repeatedly bent, lifting or peeling does not occur at the interface between the adhesive layer and the flexible member at the bent portion, and defects in appearance such as cracks and waviness are suppressed.
[0130] An example of the flexible laminated member of the present invention is shown in Figure 2. The flexible laminated member 20 in Figure 2 comprises a first flexible member 22, a second flexible member 24, and an adhesive layer 12 that is disposed between the first flexible member 22 and the second flexible member 24 and bonds these flexible members together.
[0131] Examples of the configuration of the flexible laminated member include a configuration in which both the first and second flexible members are components of a flexible device; a configuration in which the second flexible member is a flexible device and the first flexible member is a functional sheet member attached to the flexible device. Examples of the flexible device include flexible displays such as foldable displays that can be folded and rollable displays that can be rolled into a cylindrical shape. Examples of the functional sheet member include cover films, barrier films, polarizing films, retardation films, optical compensation films, brightness enhancement films, diffusion films, anti-reflection films, transparent conductive films, metal mesh films, cushion films, etc.
[0132] The first and second flexible members are members that can be repeatedly bent when used. Examples of the first and second flexible members include flexible substrate materials, functional sheet members, and display elements (organic EL modules, electronic paper modules, etc.). At least one of the first and second flexible members is preferably a display element.
[0133] (Method of manufacturing flexible laminated member) The method for producing the flexible laminated member of the present invention is not particularly limited, and examples thereof include the following methods (1) to (4).
[0134] (1) A method of peeling off a release sheet attached to one side of an adhesive sheet, adhering the exposed adhesive layer to a first flexible member, and then peeling off a release sheet attached to the other side of the adhesive sheet, adhering the exposed adhesive layer to a second flexible member, thereby obtaining a flexible laminated member. (2) A method in which an adhesive composition is applied onto one surface of a first flexible member, and if necessary, cured by a dry heat treatment to form an adhesive layer, and then a releasable surface of a release sheet is attached to the adhesive layer, and the release sheet is peeled off to expose the adhesive layer and attach it to a second flexible member, thereby obtaining a flexible laminated member. (3) A method in which an adhesive composition is applied to one surface of a first flexible member, and if necessary cured by drying and heating treatment to form an adhesive layer, and then a second flexible member is attached to this adhesive layer to obtain a flexible laminated member. (4) A method in which an adhesive composition is applied onto the releasable surface of a release sheet, and if necessary, cured by drying and heating to form an adhesive layer, and then a first flexible member is attached to the adhesive layer, and the release sheet is peeled off to expose the adhesive layer and attach the second flexible member to obtain a flexible laminated member.
[0135] In any of the above cases (1) to (4), the order in which the first flexible member and the second flexible member are used may be reversed.
[0136] The adhesive layer can be formed by using various coating methods or printing methods similar to those used in the manufacture of adhesive sheets, and the same applies to the drying and curing processes. In addition, curing may be performed as necessary. In addition, the release sheet used in the manufacture of the flexible laminated member may be the same as the release sheet used for the adhesive sheet.
[0137] (Specific examples of flexible laminated members) Hereinafter, a preferred embodiment of the flexible laminated member of the present invention will be described with reference to FIG. 3. FIG. 3 is a schematic cross-sectional view of a specific example of the flexible laminated member of the present invention. The flexible laminated member 30 shown in FIG. 3 includes a first flexible member 32, a second flexible member 34, and an adhesive layer 12 between the first flexible member 32 and the second flexible member 34, which bonds these flexible members together. The first flexible member 32 is a cover film, which has a cover film substrate 32a and a hard coat layer 32b, and the cover film substrate 32a is attached to the adhesive layer 12. The second flexible member 34 is a polarizing film.
[0138] The adhesive layer 12 is prevented from lifting or peeling off at the interface with the first flexible member 32 or the second flexible member 34 at the bent portion. Therefore, it is possible to prevent cracks from occurring in the hard coat layer 32b provided on the cover film (first flexible member) 32 when the flexible laminated member 30 is repeatedly bent.
[0139] (Cover film base material) The cover film substrate 32a is not particularly limited as long as it has flexibility and transparency. Examples of the cover film substrate 32a include a transparent polymer film and a transparent glass film. Transparency means that the total light transmittance in the visible light wavelength region is 50% or more. The total light transmittance is more preferably 85% or more. The total light transmittance is measured in accordance with JIS K7361-1 (1997).
[0140] The yellowness index (YI value) of the cover film substrate 32a is preferably 20 or less, more preferably 10 or less, and further preferably 5 or less. This makes it possible to obtain a display that displays images with high transparency and high color reproducibility. The yellowness index (YI value) is measured in accordance with JIS K 7373 (2006).
[0141] The thickness of the cover film substrate 32a is not particularly limited, but from the viewpoint of ease of handling, it is preferably 2 μm to 500 μm, and more preferably 2 μm to 200 μm.
[0142] Examples of polymer materials for the polymer film used as the cover film substrate 32a include polyester resins (polyethylene terephthalate resin, polyethylene naphthalate resin, etc.), polycarbonate resins, poly(meth)acrylate resins, polystyrene resins, polyamide resins, polyimide resins, polyacrylonitrile resins, polyolefin resins (polypropylene resin, polyethylene resin, polycycloolefin resin, cycloolefin copolymer resin, etc.), cellulose-based resins (triacetyl cellulose resin, diacetyl cellulose resin, etc.), polyphenylene sulfide resins, polyvinyl chloride resins, polyvinylidene chloride resins, polyvinyl alcohol resins, etc.
[0143] The polymer material may be composed of only one type, or may be composed of a combination of two or more types. From the viewpoint of optical properties, durability, etc., the polymer material preferably contains at least one selected from the group consisting of polyethylene terephthalate resin, polyimide resin, polycarbonate resin, poly(meth)acrylate resin, polycycloolefin resin, cycloolefin copolymer resin, and triacetyl cellulose resin, and particularly preferably contains polyimide resin. A film containing polyimide resin has flexibility that can withstand repeated bending, and is excellent in surface hardness and heat resistance. The content of polyimide resin in the polymer material is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more. The polymer material may be composed of only polyimide resin.
[0144] The cover film substrate 32a may have a single layer structure or a multi-layer structure of two or more layers. Each layer of the cover film substrate 32a may be made of only one type of the polymeric material or may be made of two or more types of the polymeric materials.
[0145] (Hard coat layer) The pencil hardness of the hard coat layer 32b is preferably 3H or more, more preferably 4H or more. The pencil hardness of the hard coat layer 32b is the pencil hardness of the surface of the hard coat layer 32b formed on one side of the cover film substrate 32a, and is measured in a state where the adhesive layer 12 is not formed on the other side of the cover film substrate 32a. The pencil hardness of the hard coat layer 32b is measured in accordance with JIS K 5600-5-4.
[0146] The thickness of the hard coat layer 32b is preferably 0.5 μm or more, more preferably 1.0 μm or more, and even more preferably 3.0 μm or more, and is preferably 10.0 μm or less, more preferably 8.0 μm or less, and even more preferably 6.0 μm or less. If the thickness is 0.5 μm or more, the pencil hardness of the cover film 32 is sufficiently ensured. If the thickness is 10.0 μm or less, the cover film is sufficiently ensured to have flexibility that can withstand repeated bending, and curling of the cover film 32 caused by the difference in thermal shrinkage between the hard coat layer 32b and the cover film substrate 32a is suppressed. The thickness of the hard coat layer 32b is the thickness of the smooth part, and when the hard coat layer contains particles, it is the thickness of the smooth part in the part without unevenness caused by the particles in the thickness direction.
[0147] From the viewpoints of high hardness, high flexibility, productivity, and the like, the hard coat layer 32b is preferably composed of a cured product of a curable composition containing an ultraviolet-curable compound.
[0148] Examples of the ultraviolet curable compound include monomers, oligomers, prepolymers, etc. having a reactive group reactive to ultraviolet light. Examples of the reactive group reactive to ultraviolet light include radical polymerization type reactive groups having an ethylenically unsaturated bond such as (meth)acryloyl group, allyl group, vinyl group, etc.; and cationic polymerization type reactive groups such as oxetanyl group, etc. Among these, the reactive group reactive to ultraviolet light is more preferably a (meth)acryloyl group or an oxetanyl group, and particularly preferably a (meth)acryloyl group.
[0149] Examples of the compound having a (meth)acryloyl group include urethane (meth)acrylate, silicone (meth)acrylate, alkyl (meth)acrylate, aryl (meth)acrylate, etc. In particular, urethane (meth)acrylate is preferred from the viewpoint of being relatively flexible and improving the flexibility of the hard coat film.
[0150] The urethane (meth)acrylate is obtained by an addition reaction between a polyol, an isocyanate compound, and a (meth)acrylate having a hydroxyl group. Examples of the polyol include polyether polyol, polyester polyol, polycarbonate polyol, etc., and can be appropriately selected from the viewpoints of flexibility, heat resistance, chemical resistance, etc.
[0151] Examples of the isocyanate compound include aromatic diisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, naphthalene diisocyanate, xylylene diisocyanate, and tetramethylxylylene diisocyanate; and alicyclic diisocyanates such as 1,4-cyclohexane diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, methylcyclohexane diisocyanate, isopropylidenedicyclohexyl-4,4'-diisocyanate, 1,3-diisocyanatomethylcyclohexane, and 4-methyl-1,3-cyclohexylene diisocyanate.
[0152] The compound having a (meth)acryloyl group may be a monofunctional (meth)acrylate having one (meth)acryloyl group in the molecule, or may be a polyfunctional (meth)acrylate having two or more (meth)acryloyl groups in the molecule. It is preferable that the compound having a (meth)acryloyl group contains a polyfunctional (meth)acrylate.
[0153] Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, amyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, 2-ethyl-2-adamantyl (meth)acrylate, bornyl (meth)acrylate, tricyclodecanyl (meth)acrylate, di Cyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, 1-naphthylmethyl (meth)acrylate, 2-naphthylmethyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy-2-methylethyl (meth)acrylate, phenoxyethoxyethyl (meth)acrylate, 3-phenoxy-2-hydroxypropyl (meth)acrylate, 2-phenylphenoxyethyl (meth)acrylate, 4-phenylphenoxyethyl (meth)acrylate, (meth)acrylate, 3-(2-phenylphenyl)-2-hydroxypropyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, butoxyethyl (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, methoxyethylene glycol (meth)acrylate,Examples of the methacrylate include ethoxyethyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate.
[0154] Examples of the polyfunctional (meth)acrylate include difunctional (meth)acrylate, trifunctional (meth)acrylate, tetrafunctional (meth)acrylate, etc. Specific examples include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate. , pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol tetra(meth)acrylate, tripentaerythritol penta(meth)acrylate, tripentaerythritol hexa(meth)acrylate, tripentaerythritol hepta(meth)acrylate, and tripentaerythritol octa(meth)acrylate.
[0155] The curable composition may or may not contain a non-UV curable resin in addition to the UV curable compound. The curable composition may also contain a photopolymerization initiator. The curable composition may also contain additives and solvents as necessary. Examples of the additives include inorganic particles, resin particles, antifouling agents, dispersants, leveling agents, defoamers, thixotropic agents, antifouling agents, antibacterial agents, flame retardants, slip agents, etc.
[0156] Examples of non-ultraviolet ray curable resins include thermoplastic resins, thermosetting resins, etc. Examples of thermoplastic resins include polyester resins, polyether resins, polyolefin resins, polyamide resins, etc. Examples of thermosetting resins include unsaturated polyester resins, epoxy resins, alkyd resins, phenolic resins, etc.
[0157] Examples of the photopolymerization initiator include alkylphenone-based, acylphosphine oxide-based, and oxime ester-based photopolymerization initiators. Examples of the alkylphenone-based photopolymerization initiator include 2,2'-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxy-cyclohexyl-phenyl-ketone, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one, and the like. -one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one, 2-benzylmethyl-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-(4-morpholinophenyl)-1-butanone, 2-(4-methylbenzyl)-2-(dimethylamino)-1-(4-morpholinophenyl)-1-butanone, N,N-dimethylaminoacetophenone, etc. Examples of acylphosphine oxide photopolymerization initiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, etc. Examples of the oxime ester photopolymerization initiator include 1,2-octanedione, 1-[4-(phenylthio)phenyl]-2-(O-benzoyloxime), ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime), etc. The photopolymerization initiator may be used alone or in combination of two or more kinds.
[0158] The content of the photopolymerization initiator is preferably from 0.1 to 10% by mass, and more preferably from 1 to 5% by mass, based on the total solid content of the curable composition.
[0159] Inorganic particles and resin particles are added for the purpose of, for example, preventing blocking in the hard coat layer, improving the hardness of the hard coat layer, imparting antiglare properties, etc. Inorganic particles include metal oxide particles made of oxides of metals such as silica, titanium, zirconium, tin, zinc, silicon, niobium, aluminum, chromium, magnesium, germanium, gallium, antimony, and platinum. These inorganic particles may be used alone or in combination of two or more kinds. Among these, titanium oxide particles, zirconium oxide particles, and tin oxide particles are preferred from the viewpoint of achieving both high hardness and transparency.
[0160] Examples of the resin particles include resin particles made of resins such as (meth)acrylic resin, styrene resin, styrene-(meth)acrylic resin, urethane resin, polyamide resin, silicone resin, epoxy resin, phenol resin, polyethylene resin, cellulose, etc. These resin particles may be used alone or in combination of two or more kinds.
[0161] Examples of the antifouling agent include fluorine-containing compounds. Examples of the fluorine-containing compounds include (meth)acrylates containing a perfluoroalkyl group. The fluorine-containing compounds can suppress adhesion of dirt and fingerprints and facilitate removal of dirt and fingerprints. The content of the fluorine-containing compounds is preferably 0.01% by mass to 15% by mass, more preferably 0.05% by mass to 10% by mass, and further preferably 0.2% by mass to 5% by mass, based on the total amount of the hard coat layer 32b. When the content of the fluorine-containing compounds is within the above range, excellent antifouling properties and antifingerprint properties can be obtained.
[0162] Examples of the solvent used in the curable composition forming the hard coat layer 32b include alcohol-based solvents (ethanol, isopropyl alcohol, n-butyl alcohol, ethylene glycol monomethyl ether, ethylene glycol monoisopropyl ether, propylene glycol monomethyl ether, diethylene glycol monobutyl ether, etc.), ketone-based solvents (methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, acetone, etc.), aromatic solvents (toluene, xylene, etc.), ester-based solvents (ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, etc.), amide-based solvents (N-methylpyrrolidone, acetamide, dimethylformamide, etc.), etc. These solvents may be used alone or in combination of two or more.
[0163] The solids concentration of the curable composition (concentration of components other than the solvent) may be appropriately determined in consideration of the coatability, film thickness, and the like, and is, for example, 1 mass % to 90 mass %, preferably 1.5 mass % to 80 mass %, and more preferably 2 mass % to 70 mass %.
[0164] (Cover film manufacturing) The cover film can be produced by forming a hard coat layer 32b on one side of the cover film substrate 32a. The hard coat layer 32b can be formed by applying a composition for forming a hard coat layer on one side of the cover film substrate 32a, and drying and irradiating with ultraviolet light, etc., as necessary.
[0165] In order to improve the adhesion between the cover film substrate 32a and the hard coat layer 32b, the surface of the cover film substrate 32a may be subjected to a surface treatment such as a corona treatment, a plasma treatment, a hot air treatment, an ozone treatment, or an ultraviolet treatment. An easy-adhesion layer may be provided on the surface of the cover film substrate 32a. Various functional layers such as a gas barrier improving layer, an antistatic layer, and an oligomer block layer may be provided on the surface of the cover film substrate 32a. Furthermore, another hard coat layer may be provided between the cover film substrate 32a and the adhesive layer 12.
[0166] The composition that forms the hard coat layer 32b can be applied by a coating method (such as reverse gravure coating, direct gravure coating, die coating, bar coating, wire bar coating, roll coating, spin coating, dip coating, spray coating, knife coating, or kiss coating), an inkjet method, or a printing method (such as offset printing, screen printing, or flexographic printing).
[0167] The drying is not particularly limited as long as it can remove the solvent used in the coating liquid, but is preferably performed at 50°C to 150°C for about 10 to 180 seconds, and particularly preferably 50°C to 120°C.
[0168] For ultraviolet irradiation, a high-pressure mercury lamp, an electrodeless (microwave type) lamp, a xenon lamp, a metal halide lamp, or any other ultraviolet irradiation device can be used. If necessary, ultraviolet irradiation may be performed in an inert gas atmosphere such as nitrogen. The ultraviolet irradiation dose is not particularly limited, but is preferably 50 mJ / cm. 2 ~800mJ / cm 2 is preferred, and 100 mJ / cm 2 ~300mJ / cm 2 is more preferred.
[0169] (Polarizing film) The polarizing film may be, for example, a polarizer having a protective film attached to at least one surface thereof via an adhesive layer. Alternatively, another optically functional film such as a retardation film or a barrier film may be laminated on the polarizer or the protective film via an adhesive layer or a pressure-sensitive adhesive.
[0170] The polarizer is a film that has the function of passing only light polarized in a specific direction, and can be, for example, a polyvinyl alcohol resin film in which iodine is oriented by uniaxial stretching. The thickness of the polarizer is, for example, 1 μm to 12 μm, preferably 1 μm to 9 μm, and more preferably 3 μm to 6 μm.
[0171] The protective film may be made of the same material as the base material used for the cover film. The thickness of the protective film is not particularly limited, but is preferably 2 μm to 500 μm, more preferably 2 μm to 200 μm, from the viewpoint of ease of handling.
[0172] The protective film may also function as a retardation film. The retardation film is an optical film that exhibits optical anisotropy, and can be formed by a method of stretching a film made of a resin that can be used for a protective film, or a method of applying a liquid crystalline compound to a substrate film, orienting the compound, and curing the liquid crystalline compound. When the polarizing film is used as a circular polarizing plate for preventing reflection in an organic EL display device, the retardation film is preferably a λ / 4 plate that provides a phase difference of λ / 4 (90°) and converts linearly polarized light into circularly polarized light. EXAMPLES
[0173] The present invention will be described in more detail below based on specific examples. The present invention is not limited to the following examples, and can be modified as appropriate within the scope of the present invention. The polymerization rate of the block copolymer, the weight average molecular weight (Mw), the molecular weight distribution (PDI), the gel fraction of the adhesive, the glass transition temperature, the shear storage modulus, the adhesive strength, the shear storage modulus and the recovery rate when strained by 400% were evaluated according to the following methods.
[0174] EHA: 2-Ethylhexyl acrylate LA: Lauryl acrylate AA: Acrylic acid HBA: 4-hydroxybutyl acrylate BTEE: Ethyl 2-methyl-2-n-butyltellanyl-propionate V-70: 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) AIBN: Azobisisobutyronitrile AcOEt: ethyl acetate
[0175] [Evaluation method] (Polymerization rate) Using a nuclear magnetic resonance (NMR) measuring device (Bruker Biospin, model: AVANCE500 (frequency 500 MHz)), 1 H-NMR was measured (solvent: CDCl3, internal standard: TMS). For the obtained NMR spectrum, the integral ratio of the peak derived from the monomer to the peak derived from the polymer was obtained, and the polymerization rate of the monomer was calculated.
[0176] (Weight average molecular weight (Mw) and molecular weight distribution (PDI)) The molecular weight was determined by gel permeation chromatography (GPC) using a high performance liquid chromatograph (Tosoh Corporation, model HLC-8320GPC). Two TSKgel Super Multipore HZ-H (Tosoh Corporation) columns were used, a tetrahydrofuran solution was used as the mobile phase, and a differential refractometer was used as the detector. The measurement conditions were a column temperature of 40°C, a sample concentration of 10 mg / mL, a sample injection volume of 10 μm, and a flow rate of 0.2 mL / min. A calibration curve was created using polystyrene (molecular weights 2,890,000, 1,090,000, 775,000, 427,000, 190,000, 96,400, 37,900, 10,200, 2,630, and 440) as a standard substance, and the weight average molecular weight (Mw) and number average molecular weight (Mn) were measured. From this measurement, the molecular weight distribution (PDI=Mw / Mn) was calculated.
[0177] (Gel fraction) The mass W1 of a wire mesh (400 mesh) cut out to a width of 50 mm and a length of 120 mm was measured. 0.1 g of the adhesive was collected and wrapped in wire mesh to prevent the adhesive from falling off to prepare a test piece, and the mass W2 of this test piece was measured. The test piece was placed in a glass bottle, 40 g of ethyl acetate was poured into it, and the bottle was shaken lightly, and then left to stand at room temperature (25°C) for 76 hours. After standing, the test piece was removed from the glass bottle and left at room temperature for 12 hours, and then dried in a vacuum oven at 100°C for 4 hours. The dried test piece was cooled to room temperature, and the mass W3 was measured, and the gel fraction was calculated using the following formula. Gel fraction (mass%) = ((W3-W1) / (W2-W1)) x 100
[0178] (glass transition temperature) The adhesive layers (adhesive materials) constituting the adhesive sheet were laminated together using a hand roller to produce a laminate with a thickness of 0.5 mm. This laminate was used as a sample, and a viscoelasticity measuring device (TA Instrument, ARES-G2) was used to measure the temperature change in the loss modulus of the adhesive material, and the peak value was taken as the glass transition temperature (Tg).
[0179] (shear storage modulus) The adhesive layers (adhesive materials) constituting the adhesive sheet were laminated together using a hand roller to produce a laminate with a thickness of 0.5 mm. The laminate was used as a sample and the shear storage modulus was measured at -40°C, 25°C, and 60°C using a viscoelasticity measuring device (TA Instrument, Discovery HR-2) in shear mode, geometry: 8 mm diameter parallel plate, axial force: 2.2 N, frequency: 1 Hz, strain: 1%. The strain γ is calculated by the following formula: γ = {(r × φ) / l} × 100 [γ: strain (%), r: radius of parallel plate (mm), φ: torsion angle (rad), l: sample thickness (mm)]
[0180] (Adhesive strength) One release sheet of the adhesive sheet was peeled off from the adhesive layer, and the corona-treated surface of a polyethylene terephthalate film (Toyobo Ester (registered trademark) film E5100: manufactured by Toyobo, thickness 50 μm) was attached to the adhesive layer surface. Then, the other release sheet was peeled off from the adhesive layer, and the adhesive layer surface was pressed onto a polyimide (PI) film (Kapton (registered trademark) 200V: manufactured by Toray DuPont, thickness 50 μm) by moving a 2 kg roller back and forth twice, and then the sheet was cut into a size of 25 mm wide and 150 mm long. The cut samples were stored for 1 hour, and then the adhesive strength of the adhesive layer to the polyimide film was measured according to the method of JIS Z 0237 (2009) using a Shimadzu Corporation precision universal testing machine "AUTOGRAPH (registered trademark) AGS-1kNX, 50N load cell" at a peel speed of 300 mm / min and a peel angle of 180°. The temperatures during storage and measurement were as follows: storage for one hour at room temperature (23°C) followed by measurement in an environment of 23°C; and storage for one hour at 60°C in a thermostatic dryer, after which the samples were immediately placed in a precision universal testing machine without cooling and measurement in an environment of 60°C.
[0181] (Shear storage modulus and recovery rate when strained 400%) The adhesive layers (adhesive materials) constituting the adhesive sheet were laminated together using a hand roller to produce a laminate with a thickness of 0.5 mm. This laminate was used as a sample and rotated to a strain of 400% with a viscoelasticity measuring device (TA Instrument, Discovery HR-2) under an environment of 23°C and 50% humidity, with a diameter of 8 mm parallel plate, axial force: 2.2 N, and angular frequency (ω) of 25 rad / sec. Shear stress was applied continuously to the sample to reach a strain of 400%, and the stress and strain after 10 minutes were measured. Next, the applied shear stress was removed to set the shear stress to 0 kPa, and the specimen was left for 10 minutes, at which point the strain (%) was measured. The recovery rate (%) was calculated from the obtained strain according to the following formula: Recovery rate (%) = {(400 - strain after 10 minutes) / 400} x 100
[0182] (adhesive layer thickness) The total thickness of the entire adhesive sheet was measured using a thickness measuring device (manufactured by Tester Sangyo, "TH-104"), and the thickness of the adhesive layer was determined by subtracting the thickness of the release sheet from this total thickness.
[0183] (Repeated bending test) One release sheet of the adhesive sheet was peeled off from the adhesive layer, and a polyethylene terephthalate (PET) film (Toyobo Ester (registered trademark) film E5100: manufactured by Toyobo, thickness 150 μm) was attached to the adhesive layer surface. Next, the other release sheet was peeled off from the adhesive layer, and the adhesive layer surface was pressed onto a polyimide (PI) film (Kapton (registered trademark) 200V: manufactured by Toray DuPont, thickness 50 μm) by rolling a 2 kg roller back and forth twice to prepare a test piece for bending test. The obtained test piece for bending test was cut into a size of 25 mm in width and 90 mm in length, and both short sides were fixed to a durability tester (Yuasa System Co., Ltd., surface-upper-body no-load U-shaped stretch tester, "DLDM111LH") so that the 150 μm thick polyethylene terephthalate (PET) film side was bent on the inside, and the specimen was bent 200,000 times at a bending diameter (inner diameter / diameter) of 7 mm and a reciprocating speed of 60 spm (60 bending times per minute). The test piece removed from the tester was visually observed and evaluated according to the following criteria. ◯: No air bubbles, lifting or peeling between the PET film or PI film and the adhesive layer, and no protrusion of the adhesive layer from the edge of the test piece. △: There is no air bubble, lifting or peeling between the PET film or PI film and the adhesive layer, but the adhesive layer protrudes from the edge of the test piece. ×: Either air bubbles are generated between the PET film or PI film and the adhesive layer, or lifting or peeling is observed, and the adhesive layer protrudes from the edge of the test piece.
[0184] <Production of copolymer> (Synthesis example 1: Copolymer No.A) In a flask equipped with an argon gas inlet tube and a stirrer, EHA (402.0 g), LA (180.0 g), AA (18.0 g), HBA (1.8 g), and AcOEt (1,357 g) were charged, and after replacing with argon, BTEE (200.9 mg) was added and the reaction was carried out at 33°C for 21 hours to polymerize.
[0185] After the reaction was completed, AcOEt was added to the reaction solution to obtain a copolymer solution containing Copolymer No. A. The obtained Copolymer No. A had a weight average molecular weight (Mw) of 700,000, a molecular weight distribution (PDI) of 1.97, and a solid content of the solution of 27.6% by mass.
[0186] (Synthesis Examples 2-5: Copolymer No.B-E) Copolymers B to E were prepared in the same manner as in the preparation of copolymer A. Table 2 shows the raw material monomers, organotellurium compounds, azo-based polymerization initiators, solvents, reaction conditions, and polymerization rates used. Table 3 shows the composition, Mw, PDI, and glass transition temperature of each copolymer.
[0187] [Table 2]
[0188] [Table 3]
[0189] <Production of Adhesive Composition> (Adhesive composition No. 1) To 100 parts by mass of the copolymer component of Copolymer No. E obtained in Synthesis Example 5, 0.25 parts by mass of an organometallic compound (Nasem aluminum) and 0.25 parts by mass of acetylacetone were added and stirred to obtain Adhesive Composition No. 1.
[0190] (Adhesive composition No. 2-24) Adhesive compositions Nos. 2 to 24 were prepared in the same manner as adhesive composition No. 1, except that the formulation was changed as shown in Tables 4, 5, and 6.
[0191] <Manufacturing of adhesive sheets> The adhesive composition was applied to the release surface of the first release sheet (PET film with release treatment on the surface, Clean Sepa (registered trademark) HY-US20A: manufactured by Higashiyama Film, thickness 75 μm) using a Baker-type applicator so that the film thickness after drying was 50 μm, and then dried at 120 ° C for 3 minutes using a thermostatic dryer. Next, the release surface of the second release sheet (PET film with release treatment on the surface, Clean Sepa (registered trademark) HY-S10: manufactured by Higashiyama Film, thickness 50 μm) was attached to the adhesive layer formed on the first release sheet, and then aging was performed at 40 ° C for 3 days to prepare an adhesive layer sandwiched between two release sheets. The evaluation results of each adhesive layer are shown in Tables 4 to 6.
[0192] [Table 4]
[0193] [Table 5]
[0194] [Table 6]
[0195] Nursem Aluminum: Manufactured by Nippon Chemical Industries Co., Ltd., Nursem Aluminum (aluminum triacetylacetonate (Al(C5H7O2)3), metal chelate compound, crosslinkable points: 9.25 mmol / g) TC-750: Matsumoto Fine Chemical Co., Ltd., Orgatics (registered trademark) TC-750 (titanium diisopropoxybisethylacetoacetate (Ti(C3H7O)2(C6H9O3)2), metal chelate compound, crosslinkable points: 9.43 mmol / g) ZC-150: Matsumoto Fine Chemical Co., Ltd., Orgatics (registered trademark) ZC-150 (zirconium tetraacetylacetonate (Zr(C5H7O2)4), metal chelate compound, crosslinkable points: 8.20 mmol / g) TETRAD (registered trademark)-C: Mitsubishi Gas Chemical Company, Inc., 1,3-bis(N,N-diglycidylaminoethyl)cyclohexane, epoxy group amount: 9.76 mmol / g) TPA-100: Asahi Kasei Corporation, Duranate (registered trademark) TPA-100 (isocyanurate of hexamethylene diisocyanate, isocyanate group amount: 5.50 mmol / g) AE700-100: Asahi Kasei Corporation, Duranate (registered trademark) AE700-100 (an adduct of hexamethylene diisocyanate, isocyanate group amount: 2.83 mmol / g) AcAc: Acetylacetone N125: Yasuhara Chemical Co., Ltd., YS Polystar N125 (terpene phenol resin)
[0196] As shown in Tables 4 to 6, the adhesive compositions No. 1 to 18 formed adhesive layers (adhesive materials) with excellent recovery rates and excellent adhesive strength. Furthermore, in a repeated bending test, the adhesive sheets having adhesive layers formed from these adhesive compositions did not show any air bubbles, lifting, or peeling between the polyester film and the adhesive layer, or between the polyimide film and the adhesive layer, and no protrusion of the adhesive layer from the end faces of the test pieces.
[0197] Adhesive compositions Nos. 19 to 23 do not contain an organometallic compound as a crosslinking agent. Adhesive layers formed from these adhesive compositions all have poor recovery rates. The adhesive composition No. 24 contains an organometallic compound as a crosslinking agent, but the amount of crosslinkable points possessed by the organometallic compound is less than 65 mol% relative to the total amount of crosslinkable points possessed by the crosslinking agent (100 mol%). The adhesive layer formed from this adhesive composition No. 24 has a poor recovery rate. Furthermore, pressure-sensitive adhesive sheets having pressure-sensitive adhesive layers formed from these pressure-sensitive adhesive compositions showed bubbles, lifting, peeling, or protrusion of the pressure-sensitive adhesive layer during repeated bending tests. [Explanation of symbols]
[0198] 10: Adhesive sheet 12: Adhesive layer 14: First flexible sheet member 16: Second flexible sheet member 20: Flexible laminated member 22: First flexible member 24: Second flexible member 30: Flexible laminated member 32: Cover film 32a: Cover film substrate 32b: Hard coat layer 34: Polarizing film
Claims
1. Contains a (meth)acrylic copolymer and a crosslinking agent, the crosslinking agent contains a metal chelate compound as an organometallic compound, the (meth)acrylic copolymer has a crosslinkable functional group that reacts with the organometallic compound, the amount of the crosslinkable functional group per unit mass of the (meth)acrylic copolymer is 5 μmol / g to 1500 μmol / g; the total amount of crosslinkable points of the crosslinking agent relative to unit mass of the (meth)acrylic copolymer is 7 μmol / g to 60 μmol / g; A pressure-sensitive adhesive composition for flexible displays, characterized in that the amount of crosslinkable points possessed by the organometallic compound is 65 mol % or more relative to a total of 100 mol % of the amount of crosslinkable points possessed by the crosslinking agent.
2. The pressure-sensitive adhesive composition for flexible displays according to claim 1, wherein the (meth)acrylic copolymer has a weight average molecular weight of 200,000 to 2,000,000.
3. 3. The pressure-sensitive adhesive composition for flexible displays according to claim 1, wherein the (meth)acrylic copolymer is obtained by living radical polymerization and has a molecular weight distribution (Mw / Mn) of 3.0 or less.
4. An adhesive material for flexible displays, characterized by being obtained by curing an adhesive composition for flexible displays described in any one of claims 1 to 3.
5. 5. The adhesive for flexible displays according to claim 4, wherein the adhesive has a shear storage modulus at −40° C. of 0.1 MPa to 1.8 MPa.
6. A pressure-sensitive adhesive sheet having an adhesive layer used for bonding one flexible member to another flexible member, and a flexible sheet member attached to at least one surface of the adhesive layer, 6. An adhesive sheet for flexible displays, wherein the adhesive layer comprises the adhesive material for flexible displays according to claim 4 or 5.
7. the adhesive sheet has a first flexible sheet member attached to one surface of the adhesive layer and a second flexible sheet member attached to the other surface of the adhesive layer, the first flexible sheet member is a first release sheet, and the second flexible sheet member is a second release sheet; The adhesive sheet for a flexible display according to claim 6 , wherein the first release sheet and the second release sheet are attached so that their respective release surfaces are in contact with the adhesive layer.
8. A flexible laminated member including a first flexible member, a second flexible member, and an adhesive layer that bonds the first flexible member and the second flexible member to each other, A flexible laminated member, characterized in that the adhesive layer is made of the adhesive material for flexible displays according to claim 4 or 5.
9. The flexible laminate member according to claim 8 , wherein at least one of the first flexible member and the second flexible member is a display element.
10. A flexible display comprising a flexible laminated member as described in claim 8 or 9.
Citation Information
Patent Citations
Adhesive and adhesive sheet using the same
JP2007138015A
Acrylic adhesive composition and adhesive film
JP2011219602A
Adhesive for repeatedly bending device, adhesive sheet, repeatedly bending laminate member, and repeatedly bending device
JP2019108498A
Adhesive for repeatedly bending device, adhesive sheet, repeatedly bending laminate member, and repeatedly bending device
JP2019108499A
Surface protective film
JP2019163478A
